Two types of cleavage, from zygote to three cells, result in different clinical outcomes and should be treated differently - Nemerovsky, Luba; Ghetler, Yehudith; Wiser, Amir; Levi, Mattan (Frontiers in Cell and Developmental Biology, 2024)
Research Question What is the utilization rate of embryos that exert inadequate zygote cleavage into three daughter cells? Design This study used a retrospective dataset from a single IVF Unit. A total of 3,060 embryos from 1,811 fresh IVF cycles were analyzed. The cleavage pattern, morphokinetics, and outcome were recorded. Only 2pn embryos, fertilized by ejaculated sperm, and cultured in a time-lapse system for at least 5 days were included. We generated three study groups according to the embryo’s cleavage pattern: (I) Control, normal cleavage (n = 551); (II) fast cleavage, zygote to three cells within 5 h (n = 1,587); and (III) instant direct tripolar cleavage (IDC) from zygote to three cells (n = 922). Results The rate of usable fast cleavage blastocysts was 108/1,587 (6.81%) and usable control blastocysts was 180/551 (32.67%). The time of PN fading and from fading to first cleavage differed significantly between the three groups. Although the pregnancy rate of control and fast cleavage blastocysts were comparable (40.35% and 42.55%, respectively), the amount of instant direct cleavage embryos that reached blastocyst stage was neglectable (only four embryos out of 922 analyzed IDC embryos) and unsuitable for statistical comparison of pregnancy rates. Conclusion Our results indicate the need to culture instant direct cleavage embryos for 5 days, up to the blastocyst stage, and avoid transfer of embryos that are fated to arrest even when their morphological grade on day 3 is acceptable, whereas fast cleavage embryos could be transferred on day 3 when there is no alternative.